What Young Lecturers in Indonesia Perceived Covid-19 Handling Related to Their Anxiety and Continuing Study Plan: A Multiple Regression Analysis - Adriani, Nour Muhammad; Labibatussolihah, Labibatussolihah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to analyze the relation between perception of government handling the Covid-19 (PG), continuing study (CS) during the pandemic and how it can predict the level of job anxiety (JA) among young teaching staff in an Indonesia university. Sixty-four participants were selected purposively from a teaching university in Indonesia. Respondents filled three-set of online questionnaires. Using IBM SPSS 26, Pearson’s correlation and multiple regression technique were used to analyze the data. The results show a statistical significance for PG and CS as predictor for JA. It is concluded that perception towards government handling of Covid-19 and continuing study had a moderate significance relationship with Job Anxiety level among young teaching staff. The PG correlates negatively while CS correlates positively to JA. Despite the fact that the nation is still suffering from the pandemic, the lecturers consider continuing their study to be more anxious than the bad policy of handling Covid-19 issues.